2011
DOI: 10.1021/pr200550p
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signatures of Lung Cancer in Biofluids: NMR-Based Metabonomics of Blood Plasma

Abstract: Lung cancer is one of the most prevalent and fatal types of cancer, with average 5-year survival rates lower than 15%, 1,2 which is mainly due to the advanced stage at which lung tumors are usually diagnosed. Indeed, when lung cancer is detected before metastasizing to lymph nodes or distant sites, the 5-year survival rates increase drastically to 60À80%, thus stressing the importance of early diagnosis. However, the majority of patients show no signs or symptoms during the initial phases of neoplastic growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
108
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 55 publications
17
108
1
Order By: Relevance
“…Significant difference was observed for LDL/VLDL signals in GBC samples as compared to control; LDL/VLDL was depleted in GBC samples. These results are consistent with the earlier published reports on various other studies on cancers (Garcia et al 2011;Rocha et al 2011). Cholesterol and cholesterol precursor molecules are required during cell division as the constituent of cell membrane and a regulated synthetic pathway of cholesterol synthesis is present.…”
Section: Discussionsupporting
confidence: 93%
“…Significant difference was observed for LDL/VLDL signals in GBC samples as compared to control; LDL/VLDL was depleted in GBC samples. These results are consistent with the earlier published reports on various other studies on cancers (Garcia et al 2011;Rocha et al 2011). Cholesterol and cholesterol precursor molecules are required during cell division as the constituent of cell membrane and a regulated synthetic pathway of cholesterol synthesis is present.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in our study reduced levels of acetate, citrate, and methanol were observed in NSCLC patients compared with COPD patients. Rocha et al reported similar results for lung cancer patients compared with healthy controls [19]. Using 13 C stable isotope-resolved metabolomic experiments in human lung cancer tissues, increased citrate levels were observed in tumors compared with healthy tissues, suggesting that the Krebs cycle is more active in tumor tissues [58].…”
Section: Metabolic Changes Associated With Lung Diseasesmentioning
confidence: 78%
“…These studies indicate that lung cancer patients exhibit perturbed metabolism of amino acids, lipids, fatty acids, glycol, and steroids [44]. The authors of a study using NMR spectroscopy of human blood plasma to detect early lung cancer stages (mainly stages I and II) reported decreased concentrations of glucose, citrate, formate, acetate, alanine, glutamine, histidine, tyrosine, valine, and methanol and elevated levels of lactate and pyruvate [19]. In addition to metabolic profiling, studies that exclusively focus on amino acid profiles using Aminoindex technology are available in the literature [45].…”
Section: Metabolic Changes Associated With Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinate dehydrogenase links the TCA cycle and oxidative phosphorylation; its deficiency causes the development of highly metastatic extra-adrenal tumors (pheochromocytomas and paragangliomas) [68]. Suppression of the TCA cycle is recognized as one of the hallmarks of cancer [69] and its impairment is implicated as critical in the mechanism of, among others, colorectal tumorigenesis [70].…”
Section: Class VII Mitocans: the Tricarboxylic Acid (Tca) Cycle-targementioning
confidence: 99%